GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 15 Oct 2019, 17:12

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If x – y = p, then 2x^2 − 4xy + 2y^2 =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

Find Similar Topics 
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58340
If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post Updated on: 08 Jul 2019, 00:56
00:00
A
B
C
D
E

Difficulty:

  25% (medium)

Question Stats:

71% (01:02) correct 29% (01:10) wrong based on 145 sessions

HideShow timer Statistics


Originally posted by Bunuel on 20 May 2017, 06:54.
Last edited by SajjadAhmad on 08 Jul 2019, 00:56, edited 2 times in total.
Added Source
GMAT Club Legend
GMAT Club Legend
User avatar
V
Joined: 12 Sep 2015
Posts: 4003
Location: Canada
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post 20 May 2017, 07:21
1
Top Contributor
Bunuel wrote:
If \(x – y = p\), then \(2x^2 − 4xy + 2y^2 =\)

(A) p

(B) 2p

(C) 4p

(D) p^2

(E) 2p^2


Given: x – y = p

2x² − 4xy + 2y² = 2(x² − 2xy + y²)
= 2(x - y
= 2(p

Answer:

Cheers,
Brent
_________________
Test confidently with gmatprepnow.com
Image
Manager
Manager
avatar
G
Joined: 12 Jun 2016
Posts: 212
Location: India
Concentration: Technology, Leadership
WE: Sales (Telecommunications)
GMAT ToolKit User
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post 20 May 2017, 07:23
Given : \((X-Y) = p\)

Squaring both sides we have -
\(X^2+Y^2-2XY = P^2\)

Needed: \(2X^2+2Y^2-4XY = ?\)

\(2X^2+2Y^2-4XY = (X^2+Y^2-2XY )+ (X^2+Y^2-2XY)\), Substituting we get
\(P^2+P^2 = 2P^2\)

Answer choice: E
_________________
My Best is yet to come!
Manager
Manager
avatar
B
Joined: 30 Apr 2013
Posts: 76
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post 27 Aug 2017, 01:15
Is it possible to divide the equation by 2 first and then applying (a+b)(a-b) formula
Math Expert
User avatar
V
Joined: 02 Sep 2009
Posts: 58340
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post 27 Aug 2017, 03:01
Director
Director
avatar
G
Joined: 09 Mar 2018
Posts: 996
Location: India
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =  [#permalink]

Show Tags

New post 08 Feb 2019, 21:18
Bunuel wrote:
If \(x – y = p\), then \(2x^2 − 4xy + 2y^2 =\)

(A) p

(B) 2p

(C) 4p

(D) p^2

(E) 2p^2



Take 2 common \(2x^2 − 4xy + 2y^2 =\)

2 * (x-y)^2

2 * p^2

E
_________________
If you notice any discrepancy in my reasoning, please let me know. Lets improve together.

Quote which i can relate to.
Many of life's failures happen with people who do not realize how close they were to success when they gave up.
GMAT Club Bot
Re: If x – y = p, then 2x^2 − 4xy + 2y^2 =   [#permalink] 08 Feb 2019, 21:18
Display posts from previous: Sort by

If x – y = p, then 2x^2 − 4xy + 2y^2 =

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  





Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne